DEVELOPMENT TENDENCIES OF USE OF INNOVATIVE TECHNOLOGIES (TAMADDUN NURI JURNALI, 2024)
This article states that one of the important pedagogical tasks is to educate young people who are knowledgeable, mature in all aspects, creative, diverse in teaching methods, who are able to competently choose modern pedagogical technologies, and study the basic mechanisms of methods and technologies based on a creative approach emphasized